Gas Hydrates Of The West Coast Of India ? A Neo-Tectonic Perspective - S. Rajendran (International Marine Minerals Society, 2005)
Gas Hydrates (Methane Hydrates) are solid, ice-like substances composed of water and natural gas. They occur naturally in areas of the world where methane and water combine at appropriate conditions of temperature and pressure and are found in ocean bottom sediments and in some permafrost areas. Besides temperature and pressure, factors like bathymetry, sediment thickness, sedimentation rates, and total organic carbon content (TOC) also control gas hydrate formation in the ocean basins. The stability of gas hydrates depends on the critical combination of high pressure and low temperature (0 - 17 bars, 0 - 25°C), which in turn is dependent on the mix of gases from which the mineral is formed. As the critical parameters can be altered by deposition, erosion, slumping, formation or melting of ice cover, rise and fall of sea level, and sudden temperature changes induced by tectonic activities, current flow, or volcanisms, the gas hydrates tend to be very unstable. The Indian offshore is promising for the occurrence of gas hydrates in a total of about 80,000 km2 area in the bathymetry range of 700 to 3000 m as reported in earlier surveys. A gas hydrate stability zone thickness map was prepared using bathymetry and sea bottom temperatures along the continental margins of India. This map is expected to provide the depth window while searching for Bottom Simulating Reflectors (BSR). The study indicates that a minimum water depth of 750 m is required for the formation of gas hydrates, above which the chances for gas hydrate occurrence appear minimal despite other favorable conditions like organic-rich sediments, etc. Single-channel seismic analog records (Gupta et al., 1998) indicate that the Western Continental Margin of India (WCMI) offers a greater promise for gas hydrate occurrences, particularly with regard to the number of BSRs traced on the analog records as compared to earlier surveys.